Scientific Research Methodology and Competency-Based Assessment of Doctoral Students in Education (Docentes 2.0 Journal, 2026)
Societal needs drive the search for solutions to problems, a process that necessitates conducting scientific research in an orderly, systematic, and progressive manner in order to address diverse requirements. The objective of this research was to determine the relationship between scientific research methodology and the competency-based assessment model among doctoral students in Education Sciences at the National University Daniel Alcides Carrión, Pasco. The inquiry was conducted within the framework of the positivist paradigm, employing the hypothetico-deductive method, a quantitative approach, and a non-experimental, correlational design. The sample consisted of 21 students, who were administered a survey regarding the variable of scientific research methodology; the validity of the questionnaire used was established through expert judgment, while its reliability was verified using the Kuder-Richardson test. The results derived from the collected data indicated the existence of a relationship between the variables. Hypothesis testing was performed using Spearman's rho correlation coefficient, and the p-value for the correlation was 0.039 (< 0.05); consequently, the null hypothesis was rejected, and the alternative hypothesis was accepted. It was therefore concluded that scientific research methodology and the competency-based assessment model share a direct relationship, as evidenced by the hypothesis test utilizing Spearman's rho statistic, which yielded a p-value of 0.039, a value lower than the 0.05 significance level.
Keywords: Competency; assessment; research; methodology; knowledge